Different wavelengths of light influence daily swimming activity in silver catfish (Rhamdia quelen) - Claudia Giannetto; Francesca Arfuso; Maria Cristina Scaglione; Giuseppe Piccione; Caterina Faggio; Federica Arrigo; Raul Delmar Cerutti (Journal of Biological Research)
The aim of this study was to investigate the daily rhythms of swimming activity in Rhamdia quelen maintained under different wavelengths of light. Thirty fish were equally divided into ten 100 liters tanks. The water temperature was maintained at 25±0.2ºC. In each tank, an infrared photocell was installed. The tanks were equipped with RGB LED strips placed at the top. Fishes were exposed to different 7 day-periods of 12/12 light/dark hours. In each period, a different light color was used: white (150 lux), red (12 lux), green (180 lux), blue (50 lux), and again white (150 lux). The application of cosinor-based techniques for the analysis of time series showed a daily rhythm of swimming activity in all tanks, in all experimental conditions. Acrophase was diurnal during the first white light schedule, on the second day of red light it was observed at the beginning of the light phase. During the green and blue schedules, acrophase was observed during the dark phase of the experimental photoperiod. In the second white schedule, it shifted in the middle of the light phase. Robustness was variable among the different lighting schedules and days of monitoring. The application of two-way of repeated measure analysis of variance showed a statistical effect of experimental lighting and day of monitoring on all rhythmic parameters. In conclusion, Rhamdia quelen lives in the deep regions of rivers, this could be the reason because the green lighting creates a reasonable environment that does not disturb the biological clock driving the swimming activity in this fish species. This information could be useful for application in aquaculture to improve fish welfare, reduce costs, and increase productivity.